Oxidative Stress in Fetuses and Newborns - Serafina Perrone; Maria Luisa Tataranno; Virginia Beretta; Giuseppe Buonocore; Eloisa Gitto (MDPI AG, 2024)
In recent years, significant research has uncovered new mechanisms by which molecules and substances that act as free radicals generate oxidative stress in the biological system, contributing to various forms of injury and disease [...]